No Benefit Adding Eleutherococcus senticosus to Stress Management Training in Stress-Related Fatigue/Weakness, Impaired Work or Concentration, A Randomized Controlled Study - Schaffler, K.; Wolf, O. T.; Burkart, M. (Pharmacopsychiatry, 2013)
Plant adaptogens are traditionally used for stress-related symptoms, but clinical evidence is inconsistent. This trial explored the effects of 120 mg/day Eleutherococcus senticosus root extract (ES), 2-day professional stress management training (SMT) and a combination of both (COM).144 participants suffering from asthenia and reduced working capacity related to chronic stress were randomized to the treatments. Validated scales and tests were used to investigate cognitive performance; feeling stressed; fatigue and exhaustion; alertness, restlessness and mood; quality of life and sleep; physical complaints and activities; and physiological stress parameters including cortisol awakening response (CAR), at baseline, after 2 and 8 weeks of treatment (German Clinical Trials Register DRKS00000692).Almost all parameters improved significantly over time without group differences. Significant differences were found in mental fatigue and restlessness, both in favor of COM vs. ES. COM was not superior to SMT in any parameter at week 8. An attenuation of the CAR was seen at week 2 without group differences. All treatments were well tolerated.Effects of adding ES to SMT are, if any, negligible.
Keywords: adaptogens; Siberian ginseng; Eleutherococcus; asthenia; stress; RCT; fatigue; concentration